Communications Identity Analysis @Viviatal in Forming Personal Branding in Tiktok - Magdalena Yohana; Maylanny Christin (Publikasi Indonesia, 2024)
This research aims to analyze @viviatal's communication identity in forming personal branding on Tiktok. This research was conducted using a qualitative approach. This research uses a case study type of research. The subject of this research is the content creator of book reviews, namely Cut Vivi Talita who has the social media account TikTok @viviatal. Data collection methods in this research are interviews, observation, literature study and documentation. Data analysis in this research uses the Identity Communication theory proposed by Michael L. Hecht. The analytical method used in this research is based on the interactive model analysis technique of Miles, Huberman, and Saldana. The research results show that Cut Vivia, through her TikTok social media account @Viviatal, has a strong personal brand and never gives up even though she comes from an underprivileged family background. Cut Vivia builds personal branding through book review content about self-development which is then linked to her life journey to provide motivational value to the audience. Based on the content shared, Cut Vivia is a visionary as seen from her ability to express opinions regarding divorce even though it is known that she has never built a household before.